Structure of the complex between lac repressor headpiece and operator DNA from measurements of the orientation relaxation and the electric dichroism. - Pörschke, D (1982)
The complex between lac repressor headpiece and short rodlike DNA fragments containing the lac operator sequence is characterised by measurements of the rotation diffusion. Using the method of electric dichroism we measure the rotation relaxation and determine changes in the length of the DNA upon ligand binding with high accuracy. According to these measurements any change in the length of the operator DNA upon binding of the first two headpiece molecules remains below 1A; the electric dichroism also remains virtually unchanged. At high degrees of (unspecific) binding we observe an increase in the rotation relaxation time, which is attributed to an increase of the apparent mean radius of the complex. As a control of our procedure for the determination of length changes we use the intercalation of ethidium bromide and arrive at an increase of the DNA length per bound ethidium of 3.2A (at 3.4A rise per base pair). The results obtained for the headpiece operator complex are not consistent with models assuming large changes of the DNA structure or intercalation of tyrosine residues.